2012
DOI: 10.5539/ass.v8n3p208
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Students towards Technical Education in Osun State

Abstract: The study examined the attitude of students towards technical education in Osun State, Nigeria. Descriptive research method was adopted by the investigator. The population of the study was made of 350 students comprising 200 males and 150 females. One validated research instrument was used to gather data. One research hypothesis was answered in the study. The results showed that: male students were more favourably disposed towards Technical Education since there was a significant difference between their mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Gender was also discovered to be one of the elements influencing the study of vocational/technical disciplines. Technical issues pique men's interest more than women do (Azubuike, 2011;Lawal, 2012). In another study, Latvian female students rated themselves higher than male students on all specified soft skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender was also discovered to be one of the elements influencing the study of vocational/technical disciplines. Technical issues pique men's interest more than women do (Azubuike, 2011;Lawal, 2012). In another study, Latvian female students rated themselves higher than male students on all specified soft skills.…”
Section: Discussionmentioning
confidence: 99%
“…Students from rural and urban locations' technical and vocational education preferences demonstrate that students from urban regions choose vocational education more than students from rural regions (Reddy et al, 2011;Lavendels et al, 2012). In contrast, one study indicated that Nigerian students from rural areas had a more favorable attitude toward technical education than metropolitan areas (Lawal, 2012). People with a business background exhibited more favorable opinions about entrepreneurship than those with an engineering background (Yasin et al, 2011) Based on the PPPM (PT) policy to solve the problem of lack of student enrolment to TVET, among the problems presented are unclear paths and articulation of TVET route, the perception that TVET is a second-class education and TVET administrative structure in the country seen unstructured as different ministries are implementing TVET Education.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors play crucial role in imparting of specific job-relevant skills for the nation's economic and labour force changes found in technical/vocational education. There are few found literatures that considered students factors in technical education settings (Azubuike, 2011;Lawal, 2012). While, Lawal's (2012), study observed that students in rural area have higher disposition towards technical education than their counterparts in the urban settings.…”
Section: International Journal Of Research Studies In Education 105mentioning
confidence: 99%
“…There are few found literatures that considered students factors in technical education settings (Azubuike, 2011;Lawal, 2012). While, Lawal's (2012), study observed that students in rural area have higher disposition towards technical education than their counterparts in the urban settings. However in both cases the study revealed that there was disproportionate relationship between students' performance and their interest in technical education.…”
Section: International Journal Of Research Studies In Education 105mentioning
confidence: 99%
See 1 more Smart Citation